Environmental Education and Community Participation: The Importance of Conservation Lessons in Teaching and Learning for Environmental Conservation Efforts in the Region of Sagara Anakan - Sugandi, Dede (ASPENSI in Bandung, Indonesia, 2013)
ABSTRACT: Conservation, as an attempt of sustainable maintenance and preservation of the environment, requires community participation. This research tries to analysis of: (1) the characteristics of Sagara Anakan watershed and territory; (2) the conducts of environmental conservation and community participation; and (3) the relevant of conservation subject for teaching and learning in Senior High School. The method employed was survey with analysis on forms of conservation and farmersâ participation. The results show that Sagara Anakan region serves for various activities, such as fishery, tourism, sport, and transportation. Conservation in the form of reforestation has not been conducted, because it is thought to cause low production of the crops. The subject of conservation is less relevant to the teaching and learning materials on environmental conservation. Fortunately, various forms of conservation have been done by the community. The forms of conservation are different for each part of the watershed, depending on the physical conditions and the possibility for land cultivation. On the other hand, to develop the teaching and learning materials, the local environment should be the resources for student learning. By this way, students will be encouraged to engage in problem-solving pertaining to the environmental conservation. KEY WORD: Forms of conservation, community participation, environmental damage, teaching and learning, Sagara Anakan region, and environmental education.Â RESUME: Artikel ini berjudul âPendidikan Lingkungan Hidup dan Partisipasi Masyarakat: Pentingnya Pelajaran Konservasi dalam Pengajaran dan Pembelajaran untuk Upaya Konservasi Lingkungan di Daerah Sagara Anakanâ. Konservasi, sebagai upaya pemeliharaan dan pelestarian lingkungan yang berkelanjutan, memerlukan partisipasi masyarakat. Penelitian ini mencoba menganalisis: (1) Karakteristik daerah aliran sungai dan wilayah Sagara Anakan; (2) perilaku konservasi lingkungan dan partisipasi masyarakat; serta (3) Relevansi subjek konservasi untuk pengajaran dan pembelajaran di Sekolah Menengah Aatas. Metode yang digunakan adalah survei dengan analisis bentuk konservasi dan partisipasi petani. Hasil penelitian menunjukkan bahwa daerah Sagara Anakan berfungsi untuk berbagai kegiatan, seperti perikanan, pariwisata, olah raga, dan transportasi. Konservasi dalam bentuk reboisasi belum dilakukan, karena diduga menyebabkan rendahnya produksi tanaman. Subjek konservasi kurang relevan dengan pengajaran dan materi pembelajaran tentang konservasi lingkungan. Untungnya, berbagai bentuk konservasi telah dilakukan oleh masyarakat. Bentuk-bentuk konservasi yang berbeda untuk setiap bagian dari daerah aliran sungai, tergantung pada kondisi fisik dan kemungkinan untuk pengolahan tanah. Di sisi lain, untuk mengembangkan pengajaran dan pembelajaran, materi muatan lokal harus menjadi sumber pembelajaran bagi siswa. Dengan cara ini, siswa akan didorong untuk terlibat dalam pemecahan masalah yang berkaitan dengan pelestarian lingkungan.KATA KUNCI: Bentuk konservasi, partisipasi masyarakat, kerusakan lingkungan, pengajaran dan pembelajaran, daerah Sagara Anakan, dan pendidikan lingkungan.About the Author: Dr. Dede Sugandi is a Senior Lecturer at the Department of Geography Education, Faculty of Social Studies Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. Corresponding author is: dsugandi58@yahoo.comHow to cite this article? Sugandi, Dede. (2013). âEnvironmental Education and Community Participation: The Importance of Conservation Lessons in Teaching and Learning for Environmental Conservation Efforts in the Region of Sagara Anakanâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.6, No.2 [November], pp.183-196. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 12, 2013); Revised (October 17, 2013); and Published (November 20, 2013). Â Â